Romantic Organicism - Armstrong, C. author. aut Link
IX, 233 p.
Keywords: Romantic Organicism attempts to reassess the much maligned and misunderstood notion of organic unity. Following organicism from its crucial radicalisation in German Idealism, it shows how both Coleridge and Wordsworth developed some of their most profound ideas and poetry on its basis. Armstrong shows how the tenets and ideals of organicism - despite much criticism - remain an insistent, if ambivalent, backdrop for much of our current thought, including the work of Derrida amongst others.